But Seriously Now … Lawyers as Agents of Happiness? The Role of the Law, Lawmakers, and Lawyers in the Realization of Bhutan's Gross National Happiness. Issue 3 (2nd September 2018) - Sonnenberg, Stephan Peter; Lham, Dema
Abstract: The concept of Gross National Happiness (GNH) – or the idea that a nation's development strategy should have as its goal the maximization of a people's happiness, rather than the maximization of their economic output – is appealingly persuasive in its humanistic simplicity. When he first articulated the concept it in 1979, the 4th Druk Gyalpo (hereditary King) of Bhutan signaled to the world that Bhutan's integration into the global community must not be premised on the blind acceptance of standard definitions of development 'progress, ' but that instead the country should be allowed to insist on its own definition of success – focused not only on economic growth but also on environmental conservation, preservation of culture and communities, and good governance. In retrospect, Bhutan's insistence on the latter course seems particularly prescient. Today, GNH is seen as one of a handful of so-called alternative visions of international development, and is attracting global attention from a growing number of policy makers, diplomats, scholars, tourists, journalists, and even religiously motivated truth-seekers. This article discusses the implications of GNH for Bhutan's lawmakers, lawyers, legal academics, and foreign development partners. This article contributes to the literature on law and development, but flips the analysis to speculate not on how legal reforms do (or do not) promote economic development, but rather how a unique national development strategy might in turn influence the nature of the legal sector.